The marketing pathfinder : key concepts and cases for marketing strategy and decision making - Stewart, David, 1948-; Saren, Michael (Chichester, West Sussex, United Kingdom : Wiley, 2014)
"This book features a unique blend of core concepts and brief, international case studies in marketing. Each chapter presents a set of core concepts, frameworks, and tools, followed by five or more short, lively international case studies illustrating how the concepts and tools can be applied in the real world. The case studies are specifically designed to encourage readers to pursue additional independent research and to encourage them to articulate and defend their decisions. Throughout, the emphasis is on the reader as a marketing professional in the thick of it and responsible for the decisions they make"--
Case AcknowledgementsChapter 3 Analysis and Understanding; It's Written in the Stars; What's Going On Out There?; Winners and Losers; We're Listening; References and Further Reading; Case Acknowledgements; Chapter 4 Understanding Why They Buy; I Think Therefore I Shop; Come Together, Right Now; Power to the People; Decisions, Decisions, Decisions; Stairway to Heaven; References and Further Reading; Case Acknowledgements; Chapter 5 How Much Are They Prepared to Pay; Making a Buck; Everything Comes at a Price; Claim to Fame; Money Makes the World Go Around; Optimized or Just Optimistic?
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Marketing -- Management; Strategic planning; Marketing -- Management; Marketing; Strategic planning; BUSINESS & ECONOMICS -- Marketing -- General; Marketing -- Management; Strategic planning; Electronic books